Co-ordination in Morphological Leaf Traits of Early Diverging Angiosperms Is Maintained Following Exposure to Experimental Palaeo-atmospheric Conditions of Sub-ambient O2 and Elevated CO2 - Evans-Fitz.Gerald, Christiana; Porter, Amanda S.; Yiotis, Charilaos; Elliott-Kingston, Caroline; McElwain, Jennifer C. (Frontiers in Plant Science, 2016)
In order to be successful in a given environment a plant should invest in a vein network and stomatal distribution that ensures balance between both water supply and demand. Vein density (Dv) and stomatal density (SD) have been shown to be strongly positively correlated in response to a range of environmental variables in more recently evolved plant species, but the extent of this relationship has not been confirmed in earlier diverging plant lineages. In order to examine the effect of a changing atmosphere on the relationship between Dv and SD, five early-diverging plant species representing two different reproductive plant grades were grown for seven months in a palaeo-treatment comprising an O2:CO2 ratio that has occurred multiple times throughout plant evolutionary history. Results show a range of species-specific Dv and SD responses to the palaeo-treatment, however we show that the strong relationship between Dv and SD under modern ambient atmospheric composition is maintained following exposure to the palaeo-treatment. This suggests strong inter-specific co-ordination between vein and stomatal traits for our study species even under relatively extreme environmental change. This co-ordination supports existing plant function proxies that use the distance between vein endings and stomata (Dm) to infer plant palaeo-physiology.